The GRPR Antagonist [99mTc]Tc-maSSS-PEG2-RM26 towards Phase I Clinical Trial: Kit Preparation, Characterization and Toxicity - Ayman Abouzayed; Jesper Borin; Fanny Lundmark; Anastasiya Rybina; Sophia Hober; Roman Zelchan; Vladimir Tolmachev; Vladimir Chernov; Anna Orlova (Diagnostics, 2023)
Gastrin-releasing peptide receptors (GRPRs) are overexpressed in the majority of primary prostate tumors and in prostatic lymph node and bone metastases. Several GRPR antagonists were developed for SPECT and PET imaging of prostate cancer. We previously reported a preclinical evaluation of the GRPR antagonist [99mTc]Tc-maSSS-PEG2-RM26 (based on [D-Phe6, Sta13, Leu14-NH2]BBN(6-14)) which bound to GRPR with high affinity and had a favorable biodistribution profile in tumor-bearing animal models. In this study, we aimed to prepare and test kits for prospective use in an early-phase clinical study. The kits were prepared to allow for a one-pot single-step radiolabeling with technetium-99m pertechnetate. The kit vials were tested for sterility and labeling efficacy. The radiolabeled by using the kit GRPR antagonist was evaluated in vitro for binding specificity to GRPR on PC-3 cells (GRPR-positive). In vivo, the toxicity of the kit constituents was evaluated in rats. The labeling efficacy of the kits stored at 4 °C was monitored for 18 months. The biological properties of [99mTc]Tc-maSSS-PEG2-RM26, which were obtained after this period, were examined both in vitro and in vivo. The one-pot (gluconic acid, ethylenediaminetetraacetic acid, stannous chloride, and maSSS-PEG2-RM26) single-step radiolabeling with technetium-99m was successful with high radiochemical yields (>97%) and high molar activities (16–24 MBq/nmol). The radiolabeled peptide maintained its binding properties to GRPR. The kit constituents were sterile and non-toxic when tested in living subjects. In conclusion, the prepared kit is considered safe in animal models and can be further evaluated for use in clinics.